Enhanced capacitive deionization properties of activated carbon doped with carbon nanotube-bridged molybdenum disulfide. (January 2023) - Sun, Jing; Li, Yun; Song, Haiou; Li, Hongxiang; Lai, Qian; Egabaierdi, Gusunkiz; Li, Qimeng; Zhang, Shupeng; He, Huan; Li, Aimin
Abstract: The shortage of freshwater supplies has restricted societal development. Capacitive deionization (CDI) is an emerging technology for desalination of seawater or brackish water, the performance of which is highly dependent on electrode materials. In this work, a molybdenum disulfide/carbon nanotube composite (CNTs-b-MoS2 ) with high capacitance was successfully synthesized using a hydrothermal method. The composite exhibited a specific capacitance of 112.79 F g −1 . To reduce costs and determine the practicality of using CNTs-b-MoS2 for CDI, we combined activated carbon (AC) with CNTs-b-MoS2 as a CDI electrode. The research demonstrated that after doping with 5% (mass ratio) CNTs-b-MoS2, the specific capacitance and electrosorption capacity of AC were significantly improved and the maximum desalination capacity of CNTs-b-MoS2 /AC reached 8.19 mg g −1 . The low dosage of CNTs-b-MoS2 combined with the high specific surface area of AC avoided the shortcomings of CNTs-b-MoS2, namely low specific surface area and high cost. Moreover, the outstanding conductivity of CNTs-b-MoS2 improved the conductivity and enhanced the adsorption capacity of AC, giving CNTs-b-MoS2 /AC potential as an advanced, low-cost CDI electrode material. Graphical abstract: Image 1 Highlights: A 3D composite of MoS2 and CNTs (CNTs-b-MoS2 ) can increase charge transfer rate. Adding a small amount of CNTs-b-MoS2 to AC will enhance capacitive deionization. CNTs-b-MoS2 /AC exhibited an enhanced CDI performance due to synergistic effect. CNTs-b-MoS2 /AC can be used as an advanced, low cost CDI electrode material.